Small-area geographic and socioeconomic inequalities in colorectal tumour detection in France. Issue 4 (July 2016) - Fournel, Isabelle; Bourredjem, Abderrahmane; Sauleau, Erik-André; Cottet, Vanessa; Dejardin, Olivier; Bouvier, Anne-Marie; Launoy, Guy; Bonithon-Kopp, Claire
Abstract : The aim of this study was to assess the impact of area deprivation and primary care facilities on colorectal adenoma detection and on colorectal cancer (CRC) incidence in a French well-defined population before mass screening implementation. The study population included all patients aged 20 years or more living in Côte d'Or (France) with either colorectal adenoma or invasive CRC first diagnosed between 1995 and 2002 and who were identified from the Burgundy Digestive Cancer Registry and the Côte d'Or Polyp Registry. Area deprivation was assessed using the European deprivation index on the basis of the smallest French area available (Ilots Regroupés pour l'Information Statistique). Healthcare access was assessed using medical density of general practitioners (GPs) and road distance to the nearest GP and gastroenterologist. Bayesian regression analyses were used to estimate influential covariates on adenoma detection and CRC incidence rates. The results were expressed as relative risks (RRs) with their 95% credibility interval. In total, 5399 patients were diagnosed with at least one colorectal adenoma and 2125 with invasive incident CRC during the study period. Remoteness from GP [RR=0.71 (0.61–0.83)] and area deprivation [RR=0.98 (0.96–1.00)] independently reduced the probability of adenoma detection. CRC incidence was only slightly affected by GP medical density [RR=1.05 (1.01–1.08)] without any area deprivation effect [RR=0.99 (0.96–1.02)]. Distance to gastroenterologist had no impact on the rates of adenoma detection or CRC incidence. This study highlighted the prominent role of access to GPs in the detection of both colorectal adenomas and overall cancers. Deprivation had an impact only on adenoma detection.